THE DIFFICULTY FACED BY THE STUDENTS IN LEARNING MODAL AUXILIARIES - Nurjanah Nurjanah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2012)
The objective of this research is to know the students’ ability in learning modal auxiliaries, especially in using forms and understanding meanings of modals. This research was conducted at SMPN 184 East Jakarta. In sample, the writer used purposive or selected random sampling, she just took 43 out of 160 second year students. She gave a test to the students, it was focused on modals. In conclusion, most of the second year students have difficulty in learning modal auxiliaries. It shows that mean score in using the form of modals is 5.90 and the mean score in understanding the meaning of modals is 5.84. Based on Gronlund standard of six, it is bad because it has not got 6. While many students got low score in the meaning is 51.16% and in the form of modals is 46.51%.Key words: Kinds of modal auxiliaries, forms of modals, meanings of modals